The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.14430/arctic4243
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Common Eider (<i>Somateria mollissima</i>) Population Quintuples in Northwest Greenland

Abstract: ABSTRACT. Common eider (Somateria mollissima) populations in Greenland severely declined throughout the 20th century. As a result, in 2001, harvest regulations were changed and the length of the hunting season was reduced. Recent data suggest that these changes have been successful, and population regrowth is occurring. In the Avanersuaq District, northwest Greenland, only one systematic survey quantifying the number of nesting eiders had previously been conducted, in 1997 and 1998. Although this district had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Within our study area in the Avanersuaq District, an ameliorating climate has been suggested as a contributing factor to recent increases in both local common eider and peregrine falcon populations, and earlier nest initiation dates for gyrfalcon (Burnham and Burnham 2011;Burnham et al 2012a, b). As daily temperatures increase, the number of days available to breed and successfully raise offspring also increases, thereby allowing for a northward expansion among many species.…”
Section: Possible Mechanisms For Observed Abundance Changesmentioning
confidence: 93%
See 4 more Smart Citations
“…Within our study area in the Avanersuaq District, an ameliorating climate has been suggested as a contributing factor to recent increases in both local common eider and peregrine falcon populations, and earlier nest initiation dates for gyrfalcon (Burnham and Burnham 2011;Burnham et al 2012a, b). As daily temperatures increase, the number of days available to breed and successfully raise offspring also increases, thereby allowing for a northward expansion among many species.…”
Section: Possible Mechanisms For Observed Abundance Changesmentioning
confidence: 93%
“…Wolstenholme and Saunders Islands are generally unsuitable for nesting waterfowl (i.e., cliffs and talus slopes) and were surveyed by boat with the exception of the large flat on the southwest side of Saunders Island, which was surveyed by foot. For information on specific island survey methodology, see Burnham et al (2012a). When applicable, five digit codes from the Greenland seabird colony database (Boertmann et al 1996) were used to identify specific islands.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations